Hubungan Power Otot Tungkai Dan Koordinasi Mata Tangan Terhadap Keterampilan Smash Pada Permainan Bola Volly Ekstrakurikuler Penjas Universitas Dehasen Bengkulu - Charles Julandra; Citra Dewi; Ajis Sumantri (Educative Sportive, 2026)
The spike (smash) is a primary attacking technique in volleyball that plays a crucial role in scoring points. Successful execution of the spike is influenced by several physical factors, notably leg muscle power and hand-eye coordination. This study aimed to determine the relationship of leg muscle power and hand-eye coordination with spiking skills among volleyball players. A correlational research method was employed, involving a population of 15 students participating in the volleyball extracurricular program. Total sampling was used as the sampling technique. The instruments utilized included a vertical jump test to measure leg muscle power, a ball toss-and-catch test to measure hand-eye coordination, and a spiking skill test. Data analysis was conducted using Pearson correlation with the aid of SPSS 25 software.The results indicated a positive and significant relationship between leg muscle power and spiking skills (r = 0.65, p < 0.05). Hand-eye coordination also showed a positive and significant relationship with spiking skills (r = 0.58, p < 0.05). Collectively, leg muscle power and hand-eye coordination were related to spiking skills (r = 0.72, p < 0.05).